Forced Displacement, Socio-Economic Impacts andMisplaced Identity of Villagers: A QualitativeExploration of Three Villages in Lahore (Journal of Asian Development Studies, 2024)
Displacement forces communities to shift their habitat which may also affect their socio-economicstatus. Very few scholarly studies documented its socio-economic impacts. Especially the impactsof forced internal displacement resulting from the development of new housing societies aremissing in the literature. To fill the gap, the present study aims to explore the socio-economicimpacts of internal displacement on villagers displaced from three villages of Lahore. For thispurpose, 18 in-depth interviews were conducted through purposively sampling. Qualitativemethodology and methods were used to achieve the research objectives, to select and recruit theresearch participants and to collect and analyze data. Internal forced displacement negativelyaffected the daily routine activities, social capital, and breakdown in the family system, detachmentand identity crises and sense of community ownership. Displacement also generated economicdependence among villagers and made their skills and expertise non-relevant in relocated settings.Hence, proper resettlement policy and plans are advised to be implemented before displacementto avoid its negative socio-economic impacts